La nouvelle loi organique sur l’information de 2012 en Algérie : vers un ordre médiatique néo-autoritaire ? - Chérif Dris (L’Année du Maghreb)
In the field of information in Algeria, the government, rather than suppress, plays the game of exclusion/marginalization on the one hand, and inclusion/ co-optation, on the other hand, thus promoting allegiance journalism. In a globalized context where information technologies break down the walls of censorship, regimes cannot manage to retain complete control over information. Rational management of information can no longer be based on censorship and stonewalling which produce adverse reactions to those expected. Instead the Algerian regime has subtly mixed official language and free expression so that receivers are less suspicious. Unlike other Arab authoritarian regimes, the Algerian government has allowed the emergence of private media and contradictory political debates. They have also democratized the use of Internet and have never stopped its access. Ultimately, we are in the presence of a neo-authoritarian media order where the motto is freedom of expression without freedom of the press.